Essential role of PU.1 in maintenance of mixed lineage leukemia‐associated leukemic stem cells. Issue 3 (12th February 2015) - Aikawa, Yukiko; Yamagata, Kazutsune; Katsumoto, Takuo; Shima, Yutaka; Shino, Mika; Stanley, E. Richard; Cleary, Michael L.; Akashi, Koichi; Tenen, Daniel G.; Kitabayashi, Issay
Abstract : Acute myeloid leukemia is a clonal malignant disorder derived from a small number of leukemic stem cells (LSCs). Rearrangements of the mixed lineage leukemia ( MLL ) gene are found in acute myeloid leukemia associated with poor prognosis. The upregulation of Hox genes is critical for LSC induction and maintenance, but is unlikely to support malignancy and the high LSC frequency observed in MLL leukemias. The present study shows that MLL fusion proteins interact with the transcription factor PU.1 to activate the transcription of CSF‐1R, which is critical for LSC activity. Acute myeloid leukemia is cured by either deletion of PU.1 or ablation of cells expressing CSF‐1R. Kinase inhibitors specific for CSF‐1R prolong survival time. These findings indicate that PU.1‐mediated upregulation of CSF‐1R is a critical effector of MLL leukemogenesis. Abstract : MLL fusions induce the rapid onset of AML by activating two classes of pathways, CSF‐1R pathway and Hox pathway.